PENGARUH KEMATANGAN EMOSIONAL, KUALITAS KEHIDUPAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI KANTOR KEMENTERIAN AGAMA KABUPATEN BATU BARA - Yunaini .; Agus Supriono; Alfi Hidayati; Asyari .; Dumai Yanti Hutauruk (Universitas Islam Islam Sumatera Utara, 2020)
Problem of this study is how influence of emotional maturity on employee’s performance. How influence of quality of work life on employee’s performance. How influence of job motivation on employee’s performance. How influence emotional maturity, quality of work life and job motivation on employee’s performance. The purpose of this study to determine and analyze the effect of emotional maturity on employee’s performance. Determine and analyze the effect of quality of work life on employee’s performance. Determine and analyze the effect of job motivation on employee’s performance. Determine and analyze the effect of emotional maturity, quality of work life and job motivation on employee’s performance. Sample in the study is 48 employee’s. Data analysis techniques used in this study is descriptive analyze and multiple linear regression analysis. The results of the study indicate emotional maturity variable has a positive and significant effect on employee’s performance. Quality of work life variable has a positive and significant effect on employee’s performance. Job motivation variable has a positive and significant effect on employee’s performance. Emotional maturity, quality of work life and job motivation variable has a positive and significant effect on employee’s performance.